PENGARUH PERENCANAAN ANGGARAN, PELAKSANAAN ANGGARAN, PENGADAAN BARANG DAN JASA, SERTA KOMPETENSI SUMBER DAYA MANUSIA TERHADAP PENYERAPAN ANGGARAN (STUDI PADA SATUAN KERJA BALAI JASA KONSTRUKSI WILAYAH V BANJARMASIN) - Putri, Yunia Isyana; Widyanti, Rahmi; Kurniaty, Kurniaty (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2024)
This research has five main purposes (1) to analyse whether budget planning partially has a significant effect on budget absorption, (2) to analyse whether partial implementation of the budget has a significant effect on absorption of the budget, (3) to analyse whether procurement of goods and services partially has a significant effect on absorption, (4) to analyse whether human resources competencies partially has a significant effect on budget absorption, and (5) to analyse whether budget planning, implementation budget, procurement of goods and services, and competence of human resources simultaneously have a significant effect on budget absorption.This research was carried out by the Work Unit of the Construction Service Center Region V Banjarmasin. Research method was descriptive quantitative. The population of this research was civil servants at Work Unit of Banjarmasin Region V Construction Service Center with the sample of 32 respondents using a purposive sampling technique. Methods of collecting data used surveys and questionnaires. The data analysis technique used the SPSS Version 25 for Window program.The results of research show that (1) budget planning has a partial and significant effect on budget absorption (2) budget execution has a partial significant effect on budget absorption, (3) goods and services have partial and significant effect on budget absorption, (4) human resources competencies have partial and insignificant effect on budget absorption, and (5) budget planning, budget execution, procurement of goods and services, and human resource competencies simultaneously have a significant effect on budget absorption.